Knockout of HDAC9 Gene Enhances Foot-and-Mouth Disease Virus Replication - Hou, Shitong; Wang, Xiangwei; Ren, Shanhui; Meng, Xuelian; Yin, Xiangping; Zhang, Jie; Tarasiuk, Kazimierz; Pejsak, Zygmunt; Jiang, Tao; Mao, Ruoqing; Zhang, Yongguang; Sun, Yuefeng (Frontiers in Microbiology, 2022)
Foot-and-mouth disease virus (FMDV) is a highly contagious viral disease that mainly infecting cloven-hoofed animals. Propagation of FMDV by cell culture is an important method to preserve viral biological and antigenic characteristics, which is crucial in FMD monitoring and vaccine production. However, only few cell lines are sensitive to FMDV and there is still a lot of room for improvement. Acetylation is an important post-translational modification, which is dynamically regulated by histone acetyltransferases (HATs) and histone deacetylases (HDACs). However, the study of relationship between FMDV and HDACs is still unclear. HDAC9 belongs to the class Ⅱ of HDACs family, in this study, HDAC9 knockout BHK-21 cells were successfully established by using CRISPR/cas9 technology. The results of karyotype analysis, growth curve analysis and morphological observation showed that the HDAC9 knockout cell line was stable in growth and morphological characteristics. After infection with FMDV, the expression of viral RNA and protein, viral titers, as well as the copies of viral RNA in HDAC9-KO cells were significantly higher than those in NC cells. Meanwhile, RNA-seq technology was used to sequence HDAC9 - KO cells and NC cells infected and uninfected with FMDV. It was found that the differentially expressed innate immune factors containing NFKBIA, SOD2, IL2RG, BCL2L1, CXCL1/2/3, IL1RAP were significantly enriched in the Jak-STAT, NOD-like receptor, Toll-like receptor, NF-κB and MAPK signaling pathway. RT-qPCR was performed to detect the expression level of differentially expressed genes and showed consistence with the RNA-seq data. These results preliminarily reveal the role of HDAC9 in host antiviral innate immune response, and the HDAC9-KO cell line also could serve as a useful tool for FMDV research.